Characterization of MDR and ESBL-producing E. coli strains from healthy swine herds of north-eastern India - SANJUKTA, R K; SURMANI, H; MANDAKINI, R K; MILTON, A A P; DAS, S; PURO, K; GHATAK, S; SHAKUNTALA, I; SEN, A (The Indian Journal of Animal Sciences, 2019)
Fecal samples (225) from apparently healthy pigs were analysed for E. coli isolation. Multidrug-resistant (MDR) isolates (42) were identified from 225 E. coli isolates. Forty isolates exhibited extended-spectrum beta-lactamases (ESBL) phenotype harbouring single to multiple-sized plasmids (1 kb to â‰¥ 25 kb). Overall blaTEM (85.7%) was the commonest genotype, followed by blaCTX-M (61.9%), blaOXA (17%) and blaSHV was not recovered. Other antimicrobial resistant genes (ARGs) identified were sul2 (100%), strA (95.2%), tetA (92.9%), sul1 (76%), aadA (71.4%), tetB (50%), cat (42.9%) and aac(3)IV (26.2%). Plasmid-mediated quinolone resistance (PMQR) positive strains totalled to 59.5% for qnrB, 19.04% for qnrS but qnrA was not detected. Integron genes were detected either singly or combined: intI1 (76.2%), intI2 (26.2%). Conjugation experiment was successful for 4 ESBL producers. The present study detected higher carriage of ESBL producing E. coli in pigs, and highlights the dominance of resistance and integron genes circulating in MDR E. coli from swine of northeast India, posing a threat of horizontal gene transfer.